Relationship of Social Media Usage and Employee Performance in a Business Process Outsourcing Company in the Philippines - Fiel Sair Caubang; Jesus Briones; Flormando P Baldovino; Rey Fernan G Refozar (Research Synergy Foundation, 2025)
The use of social media (SM) has become pervasive in the work environment, drawing attention because of its positive and negative impacts on employee performance (EP). This study investigated the relationship between SM usage and EP in a Philippine business process outsourcing (BPO) company by examining its impact on EP in terms of productivity, communication, job satisfaction, and professional development. This descriptive-quantitative study employed a researcher-structured approach to examine the relationship between SM usage and EP in a BPO company in the Philippines. The data were collected from 121 employees of the subject BPO using a researcher-structured questionnaire administered via Google Forms and communicated to respondents via Facebook Messenger and Email. Statistical tests such as frequency, percentage, standard deviation, weighted mean, and Spearman’s rank correlation were employed in the data analysis. The findings reveal that the BPO company does not have major issues related to SM usage, and it has a positive effect on EP by increasing employee productivity, improving communication, higher job satisfaction, and providing support for professional development. In addition, there is no significant relationship between problems in SM usage and the aspect of EP on productivity, communication, job satisfaction, and professional development. The researchers suggest EP enhancing strategies like implementation of SM training programs, development of SM usage policies, improvement of company recognition and communication programs, and employee active participation in professional groups. This study can serve as a guide for developing relevant initiatives and programs to improve EP in relation to SM usage in the workplace.